Role of salts on the electrical performance of ceria-based electrolytes: An overview - Grilo, João PF; Jamale, Atul; Starykevich, Maksim; Figueiredo, Filipe ML; Marques, Fernando MB (Frontiers in Materials, 2022)
This work provides an overview on established achievements and debatable findings involving Ca, Gd or Sm-doped ceria-based electrolytes, using Li2CO3, LiNO3 and Na2CO3 as sintering aid or as second phase. The performance of these materials is discussed considering the characteristics of the oxides and of the salts or derived second(ary) phases (e.g., alkali metal oxides and hydroxides, eutectic mixtures), extensively surveyed to identify influential parameters with respect to processing and electrical performance (e.g., melting and boiling points, thermal decomposition, hydrolysis). The analysis of published data highlights the possible contribution of additional charge carriers to the total conductivity, besides oxide-ion vacancies. Claimed bulk and grain boundary conductivity enhancements are deeply discussed, as well as advantages and limitations of impedance spectroscopy as characterization tool. Irrespective of controversial reasons, reports on unusual improvements of grain boundary conductivity sustain the possibility of advanced grain boundary engineering to enhance the performance of these materials.